Molecular Simulation of Hydrothermal Gasification of Digestate Sludge with Copper Catalyst Addition - Do Tuong Ha; Hien Duy Tong; Khanh-Quang Tran; Thuat T. Trinh (Chemical Engineering Transactions, 2024)
Hydrothermal gasification (HTG) has emerged as a promising technology for converting wet and low cost biomass and organic waste resources to valuable fuel gases including hydrogen and methane. In this study, hydrothermal gasification of digestate sludge, a promising approach for waste management and energy recovery from biogas plants, is investigated through molecular simulations. Copper catalyst addition is explored to enhance the process conversion efficiency. The results reveal significant improvements in gas yield and conversion rates upon copper nanoparticle catalyst addition. This work also sheds light on the catalyst aging mechanisms and offers valuable insights into optimizing hydrothermal gasification conditions for digestate sludge treatment, contributing to sustainable waste management practices and renewable energy generation.